A superconducting adiabatic neuron in a quantum regime - Bastrakova, Marina V.; Pashin, Dmitrii S.; Rybin, Dmitriy A.; Schegolev, Andrey E.; Klenov, Nikolay V.; Soloviev, Igor I.; Gorchavkina, Anastasiya A.; Satanin, Arkady M. (Beilstein Journal of Nanotechnology, 2022)
We explore the dynamics of an adiabatic neural cell of a perceptron artificial neural network in a quantum regime. This mode of cell operation is assumed for a hybrid system of a classical neural network whose configuration is dynamically adjusted by a quantum co-processor. Analytical and numerical studies take into account non-adiabatic processes as well as dissipation, which leads to smoothing of quantum coherent oscillations. The obtained results indicate the conditions under which the neuron possesses the required sigmoid activation function.
Keywords: Josephson junction; quantum neuron; quantum-classical neural networks; superconducting quantum interferometer